An analysis of efficiency improvement with the installation of energy storage in power systems - Romlie, M.F. (Institution of Engineering and Technology, 2014)
Power losses in transmission systems are proportional with square the current, where current is proportional with power transferred. For that reason, in cases where the power transfer contains a high degree of fluctuation such produced by a wind farm, power losses will be much higher than with same average power transferred smoothly. For this reason, the use of energy storage in power systems reduces transmission line losses and hence can improve the overall efficiency of the system if the energy storage losses are smaller. This paper investigates the potential to improve the overall efficiency by developing an analytical model for the energy storage and the transmission line losses depending on disturbance and confirms it via PSCAD/EMTDC simulation for idealised and real wind profile data.